David Adjaye - Adam Pendleton - Adjaye, David Sir 1966-; Pendleton, Adam 1984- (Pace, 2021)
This new volume, designed in collaboration with American artist Adam Pendleton (born 1984) and Ghanaian British artist and architect David Adjaye (born 1966), explores the blurred boundary between art and architecture. Featuring new silkscreen canvases by Pendleton and marble sculptures by Adjaye, this publication brings the artists and their works into conversation. The two collaborators discuss their respective practices and their process of working together on the creation of the exhibition at Pace, as well as notions of history, language, abstraction and space--whether architectonic or on canvas--and how these themes involve and reveal themselves in their work. Images of finished artworks are interspersed with photographs of their production, giving a behind-the-scenes look at process, from the quarrying, cutting and polishing of marble for Adjaye's works to the meeting of ink and canvas in Pendleton's studio
Titelblatt auf Seite 65
Impressum: "David Adjaye Adam Pendleton", Pace Gallery, Hong Kong, May 18-June 30, 2021
David Adjaye and Adam Pendleton in conversation, New York, December 6, 2019
Keywords: Adjaye, David -- Sir -- 1966-; Pendleton, Adam -- 1984-; Pendleton, Adam / 1984- / Exhibitions; Pendleton, Adam / 1984- / Interviews; Adjaye, David / 1966- / Exhibitions; Adjaye, David / 1966- / Interviews; Art and architecture / Exhibitions; Ausstellungskatalog -- Pace Gallery -- 18.05.2021-30.06.2021 -- Hongkong; Interview